Analisis Reaksi Pasar Modal Sebelum Dan Sesudah Pengumuman Tarif Cukai - Astriawati; Karuniana Dianta A. Sebayang; Dicky Iranto (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2023)
The capital market part of economic activity that is susceptible to being influenced by events. The aim of this research was to analyze the influence of the announcement of excise rates in 2020-2022 on the capital market reaction. The capital market reaction is measured the Abnormal Return and Trading Volume Activity. The research sample is 4 cigarette companies listed on the Indonesian Stock Exchange. This research method is event study. The event window of 5 days before and after the event. The test results show that there is a significant difference in abnormal returns in 2020 and 2022 before and after the announcement of the cigarette excise rate increase. However, there is no difference in abnormal returns in 2021 and trading volume activity in 2020, 2021 and 2022 before and after the announcement of the cigarette excise rate increase.